Mental Skills of an Athlete as a Resource of Professional Longevity in Sport - Bochaver, K.A.; Dovzhik, L.M.; Bondarev, D.V.; Savinkina, A.O. (Èksperimentalʹnaâ psihologiâ, 2021)
The aim of the study was to assess associations between dimensions of mental skills, psychological readiness and predictors of career longevity among current athletes. Mental skills dimensions were measured with the Ottawa Mental Skills Assessment Tool (OMSAT). The psychological predictors of athletic career longevity were measured with the Athletic Coping Skills Scale-28 (the ACSI-28) producing scores for seven coping skills and with the Competitive State Anxiety Inventory-2 (CSAI-2) which produced scores for confidence in competition. Overall, 253 current athletes (average age 22 years) of various competitive levels (classified to 5 groups according to the national sport classification system) participated in the study. The results showed that coping skills and confidence in competition positively associated with various range of mental skills dimensions. The competitive level was related to stress reactions, fear control, focusing, refocusing and imagery coping skills. The results suggest that some mental skills may came with experience, while the development of other mental skills may require interventions to reduce the likelihood of early termination of the professional career and achieve career longevity. The results also discussed in terms of a holistic perception of sports psychology and focuses not only on performance, but also on the well-being and sustainable development of the athletes. Исследование посвящено дифференцированной оценке уровня сформированности ментальных навыков как критерия психологической подготовленности действующих российских спортсменов различного уровня мастерства. В соответствии с современными научными подходами оценивалось двенадцать отдельных ментальных навыков спортсмена (на основании шкалы OMSAT). Они были соотнесены с психологическими предикторами спортивного долголетия спортсмена: успешным преодолением спортивного стресса (использована шкала ACSI-28, измеряющая семь копинг-навыков спортсмена) и совладанием с соревновательной тревогой (использована шкала CSAI-2, измеряющая три показателя соревновательной тревоги). В исследовании приняли участие 253 российских спортсмена (средний возраст 22 года) различного уровня мастерства: 39 спортсменов-разрядников, 67 кандидатов в мастера спорта (КМС), 110 мастеров спорта (МС), 37 заслуженных мастеров спорта и международного класса (ЗМС и МСМК). Результаты исследования показали, что копинг-компетентность (профессиональная стрессоустойчивость) и преодоление соревновательной тревоги тесно связаны с развитием ментальных навыков как психологической подготовленностью. При помощи дисперсионного анализа ANOVA было показано, что лишь часть навыков развиваются в зависимости от профессионального опыта и мастерства спортсмена, тогда как другие «не приходят с опытом», актуализируя необходимость разработки интервенций и тренингов, что позволит повысить вероятность достижения спортивного долголетия и снизить риск досрочного окончания спортивной профессиональной карьеры. Проблема исследования относится к холистическому подходу в спортивной психологии и сосредоточена не только на результативности, но также на психологическом и физическом благополучии и устойчивом развитии спортсмена.